2011
DOI: 10.1097/acm.0b013e3182254399
|View full text |Cite
|
Sign up to set email alerts
|

Promoting the Transition to Independent Scientist: A National Career Development Program

Abstract: Purpose The loss of new investigators from academic science is a “crisis” placing the future of biomedical science at risk. Failure to obtain independent funding contributes significantly to attrition from the NIH career path. The purpose of this paper is to describe the components and outcomes of the Advanced Research Institute (ARI) in Geriatric Mental Health, an NIMH grant-funded national program that targets successful transition of new investigators to independence. Method The authors first describe the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 29 publications
0
38
0
Order By: Relevance
“…This network also could be supported by the NIH (similar to the new National Research Mentoring Network). We note that this type of mentor matching has promoted the transition to independence for Geriatric Mental Health physician-scientists (28,29). With the advent of Web-based conferencing, the optimal mentors for a physicianscientist could be recruited, regardless of institutional affiliation.…”
Section: Resultsmentioning
confidence: 99%
“…This network also could be supported by the NIH (similar to the new National Research Mentoring Network). We note that this type of mentor matching has promoted the transition to independence for Geriatric Mental Health physician-scientists (28,29). With the advent of Web-based conferencing, the optimal mentors for a physicianscientist could be recruited, regardless of institutional affiliation.…”
Section: Resultsmentioning
confidence: 99%
“…Studies of specific programs, however, have found that some organizational or personal factors do contribute to this transition. 7 These organizational or program factors include: the augmentation of research funds by private sources (e.g., foundations), 8 mentoring 9,10 (particularly when centrally overseen 11 ), protected time for research training, 11 grant writing training and support, 10 time management training, 10 and access to statisticians and other experts. 10 Personal factors include: experience publishing peer-reviewed papers early in one’s career 12 and early submission of extramural grants.…”
mentioning
confidence: 99%
“…9 Indeed, the failure of an investigator to obtain independent funding is a primary cause of attrition from their academic research career path. 10 By helping investigators improve their grantsmanship skills to more effectively compete for funding, RDC hopes to bolster career stability while advancing the research enterprise at U-M.…”
Section: Rdc Strengthsmentioning
confidence: 99%